Mexico - Arnold, Helen (Zoe Books Ltd, 1996)
A child's postcards written to friends and family at home provide information-packed reports of around-the-world adventure in 20 major nations. Full-color photos on every spread, accompanied by factual observations, give youngsters a child's perspective of other countries.
Keywords: Juvenile Nonfiction; Mexico; People & Places